(untitled) (Homiletic, 2008)
In this paper Charles Campbell’s vision on the foolishness of preaching is brought into dialogue with the South African context with its history of apartheid and its struggles with issues such as poverty, HIV and AIDS, crime and most recently, xenophobia. The contribution of Campbell is discussed in terms of its significance for breaking the syndrome of silence, the revalidation of the image of the preacher as jester or clown, the role of the biblical texts as counter-testimonies to the status quo, and the rediscovery of the image of a vulnerable God.